ERP implementation and earnings management: The moderating effect of an independent board of commissioners - Devi, Suci Purnama; Aryani, Y Anni (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2024)
This research examines the moderating effect of the Independent Board of Commissioners on the relationship between implementing an enterprise resource planning system (ERP) and earnings management in non-financial companies in the Indonesia Stock Exchange. The earnings management variable is proxied through discretionary accruals, which refer to the calculation of the modified Jones model. This research used panel data from 85 companies from 2017 – 2020 to obtain a sample of 340. Employed the moderated regression analysis, the research finds that ERP implementation significantly influences the decline in earnings management. At the same time, the Independent Board of Commissioners can strengthen the relationship between the implementation of ERP systems and earnings management. This study contributes to expanding literature related to company information systems by providing evidence of the influence of ERP implementation on earnings management and how the Independent Board of Commissioner contributes to the relationship.